Multicentered study of model of anesthesia related adverse events in Thailand by incident report (The Thai anesthesia incident monitoring study): Methodology - Punjasawadwong Y. (2014)
Objective: Determine the appropriate model for incident study of adverse or undesirable events in more extensive levels from primary to tertiary hospitals across Thailand. Material and Method: The present study was mainly a qualitative research design. Participating anesthesia providers are asked to report, on anonymous and voluntary basis, by completing the standardized incident report form as soon as they find a predetermined adverse or undesirable event during anesthesia, and until 24 hours after the operation. Data from the incident report will be reviewed by three peer reviewers and analyzed to identify contributing factors by consensus. Conclusion: The THAI anesthesia incidents monitoring study can be used as a model for the development of a local system to provide review and feedback information. This should help generate real improvement in the patient care.